Lion faced water sprouts - Ghosh, Ayan (Jio Institute, 2023)
Flora Fountain was commissioned by the Agri-Horticultural Society of Western India who had initially planned the fountain to be installed at the Jijamata Udyan (formerly Victoria Garden) at Byculla. However, the site was later changed to be located just outside the former church gate where new space was made available with the filling up of the moat that surrounded the Fort walls.